2001
DOI: 10.1038/90623
|View full text |Cite
|
Sign up to set email alerts
|

The β-catenin–TCF-1 pathway ensures CD4+CD8+ thymocyte survival

Abstract: The association of trans-acting T cell factors (TCFs) or lymphoid enhancer factor 1 (LEF-1) with their coactivator beta-catenin mediates transient transcriptional responses to extracellular Wnt signals. We show here that T cell maturation depends on the presence of the beta-catenin--binding domain in TCF-1. This domain is necessary to mediate the survival of immature CD4(+)CD8(+) double-positive (DP) thymocytes. Accelerated spontaneous thymocyte death in the absence of TCF-1 correlates with aberrantly low expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
262
2
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(279 citation statements)
references
References 49 publications
13
262
2
2
Order By: Relevance
“…Signaling through the pre-T-cell receptor (pre-TCR), which controls the differentiation of immature CD4 À CD8 À CD25 þ CD44 À double-negative thymocytes into CD4 þ CD8 þ double-positive cells, stimulates CRE-dependent transcription (Grady et al, 2004). Wnt family members are expressed during various stages of T-cell development (Verbeek et al, 1995;Gounari et al, 2001;Ioannidis et al, 2001;Ishitani et al, 2003;Varas et al, 2003); the complex of b-catenin with TCF or LEF activates transcription of Tcell specific genes such as CD3e, CD4, TCRa, TCRb and TCRd (Varas et al, 2003), and is required for progression to the CD4 þ CD8 þ double-positive T-cell stage (Verbeek et al, 1995). However, Wnt signaling must be transiently switched off to ensure the rearrangement and expression of the TCRb chain before CD4 and CD8 expression (Gounari et al, 2001;Ioannidis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling through the pre-T-cell receptor (pre-TCR), which controls the differentiation of immature CD4 À CD8 À CD25 þ CD44 À double-negative thymocytes into CD4 þ CD8 þ double-positive cells, stimulates CRE-dependent transcription (Grady et al, 2004). Wnt family members are expressed during various stages of T-cell development (Verbeek et al, 1995;Gounari et al, 2001;Ioannidis et al, 2001;Ishitani et al, 2003;Varas et al, 2003); the complex of b-catenin with TCF or LEF activates transcription of Tcell specific genes such as CD3e, CD4, TCRa, TCRb and TCRd (Varas et al, 2003), and is required for progression to the CD4 þ CD8 þ double-positive T-cell stage (Verbeek et al, 1995). However, Wnt signaling must be transiently switched off to ensure the rearrangement and expression of the TCRb chain before CD4 and CD8 expression (Gounari et al, 2001;Ioannidis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate this observation, we next performed luciferase reporter assays in 293 T cells using the TOPflash luciferase reporter plasmid. Transcription of the luciferase gene in the TOPflash plasmid is under the control of a transcription factor complex consisting of members of the T-cell factor (TCF)/lymphoid enhancer factor (LEF) family of DNA-binding molecules associated with stabilized b-catenin (Verbeek et al, 1995;Gounari et al, 2001;Ioannidis et al, 2001;Varas et al, 2003). The TOPflash plasmid was cotransfected together with an expression plasmid encoding a constitutively stabilized form of b-catenin (DN87bcat; Gat et al, 1998) and either pcDNA3-HOX11, pcDNA3-HOX11 H3d, pcDNA3-HOX11 Lys55Gln or the empty pcDNA3 vector.…”
Section: Validation Of Microarray Data and Hox11 Transcriptional Mechmentioning
confidence: 99%
“…90 Tcf-1-deficient DP thymocytes were demonstrated to die more rapidly than wild-type cells, probably because of lower expression of antiapoptotic protein Bcl-x L . 89 Recently, it was shown that survival of pre-TCR þ thymocytes requires the b-catenin binding domain of Tcf-1. 92 …”
Section: Notch and Wnt Signaling In T-cell Development And T-allmentioning
confidence: 99%
“…However, b-catenin binding to Tcf-1 is essential for thymocyte differentiation, as only Tcf isoforms which contain the N-terminal b-catenin binding domain could rescue the thymic defect in Tcf-1(VII) mice. 79,89 The importance of b-catenin for T-cell development is controversial. Presence of b-catenin mRNA was detected in all thymoycte subsets.…”
Section: Notch and Wnt Signaling In T-cell Development And T-allmentioning
confidence: 99%
“…In fact, Wnt signaling through b-catenin has a positive role in the control of T-cell development, such that an absence or reduction in the Wnt signal leads to a reduction in cell proliferation rate and differentiation to the CD4 þ CD8 þ double-positive stage, whereas increased Wnt signaling through stabilization of b-catenin enables differentiation of thymocytes in the absence of a pre-TCR signal. [18][19][20] The role of the Wnt pathway in B-and T-cell oncogenesis has not been extensively investigated. b-Catenin is not detectable in normal peripheral blood T cells but is expressed in Jurkat cells, in several other leukemic cell lines and in the human T-cell lymphoma/leukemia cell line Hut102 derived from a patient with cutaneous T-cell lymphoma.…”
mentioning
confidence: 99%